The largest Quaternary inland eolian system in Brazil: Eolian landforms and activation/stabilization phases of the Xique-Xique dune field - Mescolotti, Patricia Colombo; Giannini, Paulo César Fonseca; Pupim, Fabiano do Nascimento; Sawakuchi, André Oliveira; Ladeira, Francisco Sérgio Bernardes; Assine, Mario Luis [UNESP] (Elsevier, 2023)
Eolian systems are sensitive to vegetation and climate changes, but also to the sediment supplied by neighbor depositional systems. This sensitivity is manifested in the alternation between periods of sand dune mobility and stability. In the Xique-Xique eolian system, the largest Quaternary interior dune field in Brazil (∼8000 km2), the neighboring depositional system responsible for the sand supply is the São Francisco River. We interpreted periods of dune activity and stabilization by mapping eolian landforms of this system, describing depositional facies under them and dating by optically stimulated luminescence (OSL-SAR). The stabilized parabolic landforms characterized and mapped (all formed by SE to E winds) were simple megadunes (25.5 ± 4.4 to 5.8 ± 2.0 ka), compound dunes (15.8 ± 1.2 to 5.2 ± 1.4 ka) and perched dunes (14.0 ± 1.0 and 1.2 ± 0.1 ka). We also recognized eolian plains (14.0 ± 2.1 to 6.5 ± 0.7 ka) and active parabolic dunes. Eolian deposits of undifferentiated landforms have also been described and dated (253.8 ± 19.0 to 8.2 ± 1.3 ka). The ages obtained allowed identification of two main phases of dune activity (∼60 to 18 ka and ∼16 to 5 ka) separated by a short period of stabilization marked by a paleosol (∼18 ka). The main periods of eolian activity are associated with phases of fluvial aggradation and high sediment supply, whereas dune stabilization since 5 ka is correlated with low sediment supply during the Late Holocene fluvial incision phase. The periods of eolian activity and stabilization respond not only to climate changes in the area occupied by the eolian system but mainly to local fluvial sediment supply by the river, which in turn can respond to more regional climatic controls. The Xique-Xique eolian system results from the coupling of abundant sediment supply from the fluvial system, high eastern wind speeds, and a significant wind deceleration caused by mountains on the western border of the dune field.
Keywords: Fluvio-eolian interaction; OSL dating; Parabolic dune; Sand supply